1985
DOI: 10.1128/iai.50.2.545-554.1985
|View full text |Cite
|
Sign up to set email alerts
|

Comparative studies on the effect of growth conditions on adhesion, hydrophobicity, and extracellular protein profile of Streptococcus sanguis G9B

Abstract: Streptococcus sanguis G9B was grown in continu6tis culture at different generation times and pH values in media containing either glucose or fructose and differing in the concentrations of Na+ and K'. The growth pH, carbohydrate, and cation concentration each affected the yield of organisms, their ability to adhere to saliva-coated hydroxyapatite beads, and their hydrophobicity, as measured by adhesion to hexadecane. There was no correlation between adhesion to saliva-coated hydroxyapatite beads and hydrophobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
6
0

Year Published

1988
1988
2000
2000

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 42 publications
2
6
0
Order By: Relevance
“…A chemostat study with a S. sanguis group strain showed that total extracellular protein more than doubled when culture pH was increased from 5.5 to 7.5. In addition, extracellular pro-teins which were minor or absent at one growth pH were major proteins at the other growth pH (26). In the present work when S. sanguis FSS2 was grown in the chemostat at 3 different pH levels, modulation of the specific activity of the 5 selected activities was observed (Fig.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…A chemostat study with a S. sanguis group strain showed that total extracellular protein more than doubled when culture pH was increased from 5.5 to 7.5. In addition, extracellular pro-teins which were minor or absent at one growth pH were major proteins at the other growth pH (26). In the present work when S. sanguis FSS2 was grown in the chemostat at 3 different pH levels, modulation of the specific activity of the 5 selected activities was observed (Fig.…”
Section: Discussionsupporting
confidence: 58%
“…We studied phenotypic modulation by S. sanguis FSS2 in response to changing growth conditions in the chemostat. Previous work with S. sanguis group bacteria grow^n in chemostat culture has shown that extracellular protein profiles of Streptococcus gordonii {sanguis) G9B were altered by changes in growth rate, pH and composition of growth medium (26), and that relative amounts of endo-, exo-, and amino-peptidase activities changed when S. sanguis P4A7 was switched from glucose-limited to glucose-excess (nitrogen-limited) conditions (39). In chemostat mixed culture experiments, the S. sanguis group organisms S. sanguis and Streptococcus oralis produced exoglycosidases allowing growth on mucin as the sole carbon source (43), and mixed chemostat cultures of oral bacteria increased synthesis of glycosidases when mucin was the sole carbon source (3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This difference may account for the variations in "hydrophobicity" reported by investigators using different buffer systems. It seems likely, based on our observations and those reported recently by several other investigators (23,49,50) that hydrophobic interactions represent only one of the non-covalent interactions involved in the attachment of 5*. sanguis to SHA (17,37,49).…”
Section: Discussionsupporting
confidence: 81%
“…The characterization of various wildtype strains and adherence-defective mutant strains of S. sanguis has provided evidence that the ability of cells to adhere to SHA (3,8,12) or to coaggregate with actinomycetes (17) is associated with the hydrophobicity of the cell surface. Notwithstanding this, some mutants of 5. sanguis that are defective in adherence have increased hydrophobicity (8), and Knox et al (20) were unable to correlate adherence with hydrophobicity for cells grown under a variety of different conditions. The results in this paper support the view that cell surface hydrophobicity is a strong determinant in S. sanguis adherence.…”
Section: Discussionmentioning
confidence: 99%